Comparing drawing under instructions with image copying for mild cognitive impairment (MCI) or dementia screening: A meta‐analysis of 92 diagnostic studies. (1st February 2022) - Bat, Baker Kwok Kwan; Chan, Joyce YC; Chan, Tak Kit; Huo, Zhaohua; Yip, Benjamin HK; Wong, Martin CS; Tsoi, Kelvin KF
Abstract: Background: Drawing is a major component of cognitive screening for dementia. It can be performed without language restriction. Drawing pictures under instructions and copying images are different screening approaches. The objective of this study was to compare the diagnostic performance between drawing under instructions and image copying for MCI and dementia screening. Method: A literature search was carried out in the OVID databases with keywords related to drawing for cognitive screening. Study quality and risk of bias were assessed by QUADAS‐2. The level of diagnostic accuracy across different drawing tests were pooled by bivariate analysis in a random effects model. Summary estimates of sensitivity and specificity with 95% CI and prediction region were presented in a hierarchical summary receiver operating characteristic (HSROC) curve. The area under the hierarchical summary receiver‐operating characteristic curve (AUC) was constructed to summarize the diagnostic performance. Result: Ninety‐two studies with sample size of 22, 085 were included. The pooled results for drawing under instructions showed a sensitivity of 79% (95% CI: 76 – 83%) and a specificity of 80% (95% CI: 77 – 83%) with AUC of 0.87 (95% CI: 0.83 – 0.89). The pooled results for image copying showed a sensitivity of 71% (95% CI: 62 – 79%) and a specificity of 83% (95% CI: 72 – 90%) with AUC of 0.83 (95% CI: 0.80 – 0.86) (Fig. 1). Subgroup analysis for the diagnostic accuracy for MCI and dementia showed that both drawing under instructions and image copying have better diagnostic performance for patients with dementia. The AUC of drawing under instructions and image copying for patients with dementia were 0.88 (95% CI: 0.85 – 0.91) and 0.85 (95% CI: 0.82 – 0.88) and the AUC for patients with MCI were 0.77 (0.73 – 0.80) and 0.73 (95% CI: 0.69 – 0.77), respectively. Most of the studies used clock‐drawing test as the screening test. Conclusion: Drawing under instructions showed a similar diagnostic performance when compared with image copying for cognitive screening and the administration of image copying is relatively simpler. Self‐screening for dementia is feasible to be done at home in the near future.